2022
DOI: 10.3389/fimmu.2022.850998
|View full text |Cite|
|
Sign up to set email alerts
|

Role of the CXCL13/CXCR5 Axis in Autoimmune Diseases

Abstract: CXCL13 is a B-cell chemokine produced mainly by mesenchymal lymphoid tissue organizer cells, follicular dendritic cells, and human T follicular helper cells. By binding to its receptor, CXCR5, CXCL13 plays an important role in lymphoid neogenesis, lymphoid organization, and immune responses. Recent studies have found that CXCL13 and its receptor CXCR5 are implicated in the pathogenesis of several autoimmune diseases, such as rheumatoid arthritis, multiple sclerosis, systemic lupus erythematosus, primary Sjögre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 198 publications
(315 reference statements)
0
41
0
Order By: Relevance
“…In our study, the selected patients were all newly diagnosed IBD patients at the early stage of the disease. In addition, CD4+CXCR5+ T cells included not only CD4+CXCR5+Foxp3- T follicular helper (Tfh) cells, but also CD4+CXCR5+Foxp3+ T follicular regulator (Tfr) cells ( 24 , 25 ). Furthermore, Cxcl13 -/- knockout mice were used to construct DSS-induced colitis model to verify the role of CXCL13 in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the selected patients were all newly diagnosed IBD patients at the early stage of the disease. In addition, CD4+CXCR5+ T cells included not only CD4+CXCR5+Foxp3- T follicular helper (Tfh) cells, but also CD4+CXCR5+Foxp3+ T follicular regulator (Tfr) cells ( 24 , 25 ). Furthermore, Cxcl13 -/- knockout mice were used to construct DSS-induced colitis model to verify the role of CXCL13 in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…This brings us to CXCL13 as a soluble part of the CXCL13/CXCR5 immune axis, which is, as is the case for cTfh cells, physiologically detectable in blood and increased upon immune activation in the same contexts of infection, vaccination, and autoimmune disorders [ 34 , 75 , 76 ]. Plasma CXCL13 elevations, contrary to their cellular counterparts, are neither antigen- nor disease-specific.…”
Section: The Cxcl13/cxcr5 Immune Axis In the Peripheral Immune Systemmentioning
confidence: 99%
“…With regard to autoimmunity, CXCL13 elevations in the blood occur in SLE, RA, SS, MS, and MG, and are proposed biomarkers for disease activity, treatment response, and treatment targets for autoimmune disorders [ 30 , 34 , 80 , 81 , 82 ]. Preclinical therapeutic intervention studies with an anti-CXCL13 monoclonal antibody accordingly showed comparable effectiveness compared to standard treatments in mouse models of RA (collagen-induced arthritis) and MS (experimental autoimmune encephalomyelitis) [ 82 ].…”
Section: The Cxcl13/cxcr5 Immune Axis In the Peripheral Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this this version posted December 14, 2022. ; https://doi.org/10.1101/2022.12.13.22283427 doi: medRxiv preprint autoimmune diseases (Pan et al 2022) and hematologic cancers (Hussain et al 2013). Due to its plethora of activities and effects upon several cell types, CXCL13 can be regarded as a biomarker of both lymphoid (humoral and cellular) and myeloid cell activation and networking.…”
Section: Introductionmentioning
confidence: 99%